The Effects of Administration of Mangosteen Pericap's Ethanolic Extract and Xanthone on Angiogenesis of Gastric Ulcer Healing in Wistar Rats Observed Through the Increase in the level of NO and VEGF and CD-31 Expressions - Ika Kustiyah Oktaviyanti; Djanggan Sargowo; Mohammad Aris Widodo; Karyono Mintaroem (The Prodia Education and Research Institute (PERI), 2011)
BACKGROUND: NSAIDs can cause gastric ulcer or may delay the healing of it. Upon exposure to indomethacin, gastric ulcer can occur due to oxidants. Mangosteen rind contains xanthone, which is a natural antioxidant. Administration of this antioxidant may increase angiogenesis that can accelerate healing of gastric ulcer.METHODS: This study used an experimental method with randomized post test control only design using Wistar rats. The rats were put on fasting for 24 hours, then a single dose of 30mg/kg body weight (BW) Indomethacine was given. The rats were divided into control group and treatment group. The treatment group was further divided into two subgroups: one group was given a daily 200 mg/kg BW mangosteen pericap extract, and the other group was given 35 mg/kg BW Xanthone. Both the control group and treatment group were decapitated on the 3rd day, 6th day and 12th day, respectively. After decapitation, the stomach of each rat was taken and divided into two portions, one portion was used for NO examination by ELISA, and the other portion for hispathological examination and immunohistochemical analysis for assessing CD 31 and VEGF expressions.RESULTS: Administration of mangoosteen pericap and xanthone could accelerate healing of gastric ulcers as compared with the control, as shown by the decrease in the severity level of the ulcers. Mangoosteen pericap and xanthone could also increase NO, VEGF expression, and CD-31 as compared with the control, especially on the 3rd day of treatment. Explanation of this finding might be that the antioxidants contained in the mangoosteen pericap or in xanthone could bind with radical superoxide and accelerate release of free NO. The increase of NO caused increase of VEGF and CD-31 that could accelerate angiogenesis, which eventually could accelerate healing of the gastric ulcers.CONCLUSIONS: The effect of mangosteen pericap's extract and xanthone can improve healing of gastric ulcers by increasing nitric oxide and also can increase angiogenesis as shown by the increase of VEGF and CD-31 expressions.KEYWORDS: mangosteen, healing, gastric Ulcer, angiogenesis